2015
DOI: 10.1002/adem.201400521
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of the Commercial Mg‐PSZ Powders

Abstract: Using X-ray diffraction and scanning electron microscopy two commercial Mg-PSZ ceramics were studied regarding their thermal stability at 1350°C. The Mg-PSZ material was investigated in asreceived, sintered, and powdered states. Drastic increasing of the m-ZrO 2 content was observed for the asreceived powders. Whereas the Mg-PSZ ceramics sintered at 1600°C exhibit certainly better thermal stability. Two mechanisms of thermal destabilization were defined using observations of the sintered Mg-PSZ material. Influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The diffusion of the stabilizer magnesia and the formation of silicates is well known in such metal matrix composites. [ 13,22,24,25 ] In the present study, (Mg, Mn)Si 2 O 4 has been identified by the EBSD analysis.…”
Section: Resultsmentioning
confidence: 85%
“…The diffusion of the stabilizer magnesia and the formation of silicates is well known in such metal matrix composites. [ 13,22,24,25 ] In the present study, (Mg, Mn)Si 2 O 4 has been identified by the EBSD analysis.…”
Section: Resultsmentioning
confidence: 85%